COMPARATIVE SCIENTIFIC ANALYSIS ON THE POLITICAL AND SOCIAL SITUATION OF THE JAPAN - KAZAKH PEOPLE IN XVIII-XIX CENTURIES - Куанбай, О.Б. (Asian Journal "Steppe Panorama", 2025)
In this article, on the basis of archival documents, a comparative scientific analysis of the political and social situation of the Japanese people during the Tokugawa period and the Kazakh people during the colonial policy of the Russian Empire is carried out. Each scientific fact, confirmed by historical documents, reveals the essence of the article. The article also provides a comparative scientific and expert assessment of domestic and foreign policy and the life of the Japanese and Kazakhs. Historical important events and political and administrative positions of the Japanese and Kazakh peoples are analyzed. Despite the geographical distance between them, archival data show that the Japanese-Kazakh people had the same problems with different taxes during the era of feudal imperialism. Not only the political and social position of the Japanese Kazakh people, but also the spiritual position did not remain outside the scope of scientific research. This topic still requires deep study.